2015
DOI: 10.1111/ped.12638
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, medical genetics, diagnosis and treatment of harlequin ichthyosis in Japan

Abstract: Ichthyoses are a group of disorders marked by whitish, brown or dark-brown scales on the skin of almost the whole body. Harlequin ichthyosis (HI) is the most severe form. Neonatal death from HI was once common. Due to intensive neonatal care and, probably, to the early introduction of oral retinoids, HI outcome has improved. For definitive diagnosis and the exclusion of other disorders, such as lamellar ichthyosis, which also shows a collodion baby phenotype, it is helpful to refer to electron microscopy of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
0
27
0
3
Order By: Relevance
“…They concluded that early retinoid therapy as well as intensive neonatal care improve the prognosis of HI. 3 In our case, we believe that early retinoid therapy and the administration of antibiotics led to a favorable prognosis.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…They concluded that early retinoid therapy as well as intensive neonatal care improve the prognosis of HI. 3 In our case, we believe that early retinoid therapy and the administration of antibiotics led to a favorable prognosis.…”
Section: Discussionmentioning
confidence: 57%
“…In Japan, Shibata and Akiyama carried out a nationwide review of HI, and reported that among the 16 HI babies born between 2005 to 2010, 13 survived (81.3%) and three died (18.7%). They concluded that early retinoid therapy as well as intensive neonatal care improve the prognosis of HI . In our case, we believe that early retinoid therapy and the administration of antibiotics led to a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Close monitoring of body temperature is essential as dysregulation of body temperature can occur due to impaired sweating from obstruction of sweat glands by the thickened stratum corneum 2. Ventilatory support may be required if the rigid chest wall restricts breathing and pulmonary function 1.…”
Section: Discussionmentioning
confidence: 99%